Utilization of Butterfly Pea Flowers for Food Applications with Antioxidant Content in Ciparigi Village, North Bogor District, Bogor City - Nuraeni, Farida; Tri Aminingsih (Jurnal Pengabdian Masyarakat Inovatif, 2025)
Ciparigi Village is one of the Villages in the North Bogor District, Bogor City, West Java, with an area of 160.72 Ha. The population of Ciparigi Village is 18,324 people consisting of 9,092 men (49.62) and 9,232 women (50.38) with a total of 4,909 Family Heads. The population density in this Village in 2008 was 11,401 people per km2. When viewed from the activities of each working group in Ciparigi Village, it is still very small, this is probably due to the lack of delivery of various information or development of its members' skills in the form of counseling and training to the community. The solution offered by the University in this case the Chemistry Study Program, FMIPA, Pakuan University, is to provide counseling on the use of butterfly pea flowers to be applied to several food preparations. The lack of public knowledge, especially the family empowerment and welfare group in Ciparigi Village, in processing and optimizing the potential of butterfly pea flowers needs to be improved through socialization and training. The output targets to be achieved include publication in the LPPM Journal of Pakuan University, publication in the mass media, and increasing skills in making food products with butterfly pea flowers. The bright blue color of butterfly pea flowers is very attractive and easy to consume, mothers can produce butterfly pea flower syrup, butterfly pea flower tea and butterfly pea flower pudding. Butterfly pea flowers contain various active compounds that are beneficial for health, such as: anthocyanins - natural pigments that function as antioxidants to protect body cells from damage caused by free radicals, flavonoids-compounds that can help reduce inflammation and boost the immune system, cyclic peptides-Known to have antimicrobial and anticancer properties, phenolic acids-play a role in maintaining heart health and reducing the risk of chronic diseases.